Being a thing : an analysis of neccessitist metaphysics in first-order quantified modal logic : [a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Philosophy at Massey University, New Zealand] - Hawkins, Nathan (Massey University, 2016)
Timothy Williamson, a necessitist, argues that ‘necessarily everything is necessarily something’. However his claim is ambiguous regarding the kind of modal structure it endorses, with each structural candidate resulting in distinct metaphysical stakes. In this piece I outline each of the structural candidates and analyse them —both logically and metaphysically—within and against Kripkean first-order free logic. I show that the problems Williamson raises with contingentist logic similarly cause problems inside necessitist models. I conclude with a surprising suggestion: a modal logic that treats variables as individual-world pairs, along with a radical form of necessitism that treats quantification as metaphysically primitive.